Updating Beliefs: Are economic agents inspired by rational action or according to ones hopes and fears?. (2004)
The purpose of this investigation was to simulate a real life scenario and explore the way economic agents update their beliefs. Do they update according to what they hope? Or do they update inspired by rational behavior? We mimicked the environment which a recently high school graduate faces when entering college to see how astudent updates his beliefs in regards to his classroom position. We examined how economic agents envisage themselves through and through college and see if they update their beliefs about a hypothesis A in the lightof new evidence B, or if they update their beliefs subject to what they choose they hope. In this sense we explored the possibility of setting a side the neoclassical assumption that agents are anything more than hyperrational naïve optimizers acting on perfect (and in some cases, limited information) in order to turn back to an older tradition in economic theory, that is agents are recognizably human.